A Systematic Review Factors Influencing Patient Utilization of Telepharmacy Services - Azami S, Lalu M. Rifqi; Andanalusia, Mahacita; Arimbawa, I Wayan Agus; Mayada, Silhiyatun; Bimantika, Fara Mutia (Journal of Computer Science and Informatics Engineering (J-Cosine), 2025)
The advancement of telepharmacy has significantly transformed the delivery of pharmaceutical services, particularly in regions with limited healthcare access. This systematic review aims to identify key factors influencing patients' utilization of telepharmacy services. A comprehensive literature search was conducted across PubMed, ScienceDirect, and Google Scholar, following PRISMA guidelines. Inclusion and exclusion criteria were applied to select relevant studies published between 2015 and 2025. Thematic synthesis of five eligible studies revealed five key factors affecting telepharmacy adoption: perceived practicality, efficiency, education level and age, knowledge, and trust. These factors align with the Technology Acceptance Model (TAM), highlighting the roles of perceived usefulness, ease of use, and psychological readiness. Strengthening digital literacy, infrastructure, and trust-building interventions is essential to enhance telepharmacy utilization, especially in developing countries like Indonesia. The findings provide valuable insights for designing patient-centered telepharmacy policies and services. Keywords: Telepharmacy, utilization factors, patient acceptance, Technology Acceptance Model, healthcare access.